"Houston, We Have a Lawsuit": A Cautionary Tale for the Implementation of Value-Added Models for High-Stakes Employment Decisions. (June 2020) - Paige, Mark A.; Amrein-Beardsley, Audrey
Until recently, legal challenges to the use of value-added models (VAMs) in evaluation and teacher employment decisions in federal court had been unsuccessful. However, in May 2017 a federal court in Texas ruled that plaintiff-teachers established a viable federal constitutional claim to challenge the use of VAMs as a means for their termination in Houston Federation of Teachers v. Houston Independent School District . Houston represents a significant departure from prior federal court rulings that upheld the constitutionality of VAMs to terminate teachers on the basis of poor performance. The Houston court found that the districts' refusals to release the underlying data of VAM ratings used to terminate those teachers violated the teachers' procedural due process rights. By denying access to the code, teachers could not protect against the government's making a mistaken deprivation of their property right to continued right to employment. The authors discuss Houston and its potential impact, limitations, and significance.